IOTA-Carrageenan as an additive in pound cake - Vela, Josie Tajan
The effects of the different levels of iota-carrageenan i.e. 0.2%, 0.6%, and 1.2% on pound cake were investigated. Objective and subjective tests showed that 0.2% emerged as the most desired level of carrageenan by weight (of the sample) added in the product. The 0.2% sample was then compared with the control by sensory evaluation. Significant effects of iota-carrageenan were observed on the sample being tested. The incorporation of the carrageenan in pound cake resulted in the increase of volume, improvement of texture, and greater yield of the product.